A new versatile peroxidase from Pleurotus. (May 2001) - Ruiz-Dueñas, F. J.; Camarero, S.; Pérez-Boada, M.; Martínez, M. J.; Martínez, A. T.
Abstract : Lignin peroxidase (LiP) and manganese peroxidase (MnP) have been investigated in Phanero-chaete chrysosporium. A third ligninolytic peroxidase has been described in Pleurotus and Bjerkandera. Two of these versatile peroxidases (VPs) have been cloned, sequenced and characterized. They have high affinity for Mn 2+, hydro-quinones and dyes, and also oxidize veratryl alcohol, dimethoxybenzene and lignin dimers. The deduced sequences show higher identity with Ph. chrysosporium LiP than MnP, but the molecular models obtained include a Mn 2+ -binding site. Concerning aromatic substrate oxidation, Pl. eryngii VP shows a putative long-range electron transfer pathway from an exposed trytophan to haem. Mutagenesis and chemical modification of this tryptophan and the acidic residues forming the Mn 2+ -binding site confirmed their role in catalysis. The existence of several substrate oxidation sites is supported further by biochemical evidence. Residue conservation in other fungal peroxidases is discussed.